SCENARIO MODELING OF PROCESS OF MOVEMENT OF FINANCIAL FLOWS BETWEEN INSTITUTIONAL SECTORS IN THE REGIONAL TERRITORIAL SYSTEM - I. V. Naumov (Финансы: теория и практика)
Topic. The article substantiates the necessity of use of scenario approach in the study and prediction of the process of movement of financial flows between institutional sectors in the territorial system. It allows detecting negative trends in the movement of financial resources between sectors of the economy, and form a picture of various scenarios of transformation in the process of movement of financial flows between them under the influence of different factors. Purpose. We try to find regularities and causal relationships in the process of movement of financial flows between institutional sectors in the regional system and to create on their basis the predictive scenarios of a possible transformation matrix of financial flows between sectors.Methodology. The study is based on the principles and theoretical-methodological fundamentals of the scenario simulation, and includes the following stages: formation of initial matrix of financial flows between institutional sectors in the region; the study of the patterns of their movements; an economic-mathematical modeling of processes of movement of financial flows between institutional sectors by using multiple nonlinear regression analysis to establish causal relationships among these processes; the search for possible deviations in the movement of financial flows generated by the model and development on their basis of different scenarios of the transformation matrix of financial flows. There was used tool for econometric analysis by the method of least squares to eliminate multicollinearity. Results. We described the main directions and tendencies of the financial flows’ movement between sectors in theSverdlovsk region in the periods of increase of the crisis phenomena in the economy and after stabilization of the economic development. We generated predictive scenarios of a possible transformation matrix of financial flows between sectors and modeled the main scenarios of the transformation matrix of financial flows between sectors.Conclusions. For stabilization of the financial development of institutional sectors in theSverdlovsk region, it is necessary: to attract the financial resources for the nonfinancial corporate sector through the increased investment of institutional sectors in debt securities of industrial enterprises. It is necessary to attract additional funds for the deposits of the financial corporations’ sector, as well as additional capital through the emission and sale of the shares of the banking sector. These activities will also help to stabilize the financial-economic situation and other institutional sectors.